2012
DOI: 10.1088/0004-637x/757/1/7
|View full text |Cite
|
Sign up to set email alerts
|

WISEDETECTIONS OF DUST IN THE HABITABLE ZONES OF PLANET-BEARING STARS

Abstract: We use data from the Wide-field Infrared Survey Explorer (WISE) all-sky release to explore the incidence of warm dust in the habitable zones around exoplanet-host stars. Dust emission at 12 and/or 22 μm (T dust ∼ 300 and/or ∼150 K) traces events in the terrestrial planet zones; its existence implies replenishment by evaporation of comets or collisions of asteroids, possibly stirred by larger planets. Of the 591 planetary systems (728 extrasolar planets) in the Exoplanet Encyclopaedia as of 2012 January 31, 350… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 40 publications
1
29
1
Order By: Relevance
“…At a 3σ sensitivity level of about 1000 times the level of the zodiacal emission in the short IRS wavelength band (8.5-12 µm), the authors found a success rate for excesses of about 1%. This occurrence rate, recently confirmed by WISE mid-infrared photometry (Morales et al 2012;Padgett et al 2013), is in stark contrast to the present study, and points again to a non-solar system morphology for the exozodiacal discs detected at K band.…”
Section: Sensitivity Of Fluor and Comparison With Other Studiescontrasting
confidence: 52%
“…At a 3σ sensitivity level of about 1000 times the level of the zodiacal emission in the short IRS wavelength band (8.5-12 µm), the authors found a success rate for excesses of about 1%. This occurrence rate, recently confirmed by WISE mid-infrared photometry (Morales et al 2012;Padgett et al 2013), is in stark contrast to the present study, and points again to a non-solar system morphology for the exozodiacal discs detected at K band.…”
Section: Sensitivity Of Fluor and Comparison With Other Studiescontrasting
confidence: 52%
“…Photometric monitoring indicated that it has an inclination of  27 and a rotation period of 8.45 days (Broeg et al 2007). It is one of the most studied CTTSs due to many features indicative of active accretion onto the star from a circumstellar disk, such as brightness variations (e.g., Friedrich & Schöffel 1971;Appenzeller et al 1978;Broeg et al 2007;Donati et al 2012), inverse P-Cygni profiles (e.g., Appenzeller et al 1978;Bertout et al 1982;Batalha et al 2001), optical veiling (e.g., Batalha et al 2001;Seperuelo Duarte et al 2008), very intense magnetic field (e.g., Donati et al 2012;JohnsKrull et al 2013), and strong excess from near-to far-infrared (e.g., Mendoza 1968;Hughes et al 1994;Kessler-Silacci et al 2006;McClure et al 2012;Morales et al 2012). The accretion disk was first imaged at 1.3 mm dust continuum emission by Dai et al (2010) using the Submillimeter Array.…”
Section: Gq Lup a And Bmentioning
confidence: 99%
“…Among these stars, a few dozen are also known to harbor planets (Lawler and Gladman 2012;Morales et al 2012;Bonsor et al 2013). …”
Section: Introductionmentioning
confidence: 99%